Perancangan Tata Letak Fasilitas Pabrik Tempe Berdasarkan GMP (Good Manufacturing Practices) - Yusuf Mauluddin; Elisa Nurlisina (Jurnal Kalibrasi, 2026)
A company needs to ensure good quality by applying several standards to demonstrate that it meets established quality benchmarks. These standards include SNI (Indonesian National Standard), PIRT (Home Industry Food Certification), and GMP (Good Manufacturing Practices). One of the food industries that still thrives in the culinary world today is the tempeh industry. Tempeh is a traditional food made from soybeans that are processed into a nutritious fermented product. A factory will operate efficiently if its layout and facilities support production activities.The layout of factory facilities is intended to organize the factory in a way that enhances the effectiveness of the production process. A good layout also facilitates efficient material handling and product movement.The purpose of this study is to examine the factory layout of a tempeh production facility based on GMP (Good Manufacturing Practices). This research uses a conventional method validated by CRAFT processing with the aid of Excel add-ins, and GMP serves as the reference in the layout planning process.The results of the study show that the optimal layout for the production department follows the flow of the tempeh production process. Based on this layout, a design was created by establishing rules and facilities in accordance with GMP.